AnonShield: Scalable On-Premise Pseudonymization for CSIRT Network Vulnerability Data - Kapelinski, Cristhian; Lautert, Douglas; Machado, Beatriz; Kreutz, Diego; Ferrão, Isadora Garcia (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
We present AnonShield, a high-throughput, on-premise pseudonymization system for network vulnerability scan reports that combines GPU-accelerated NER, streaming processing, caching, and schema-aware configuration. Evaluated on datasets up to 550 MB (70,951 records), AnonShield reduces processing time from over 92 hours to under 10 minutes (up to 738× speedup), reaching F1 = 94.2% and Recall = 96.4% on a specialist-annotated validation set. Our results show that scalable pseudonymization of network vulnerability data is feasible without sacrificing analytical utility, enabling compliant data sharing in operational CSIRT environments.